Delta Air Lines valuation - Monteiro, Catarina Oliveira (2020)
Delta Air Lines is a company within the airlines industry, mainly operating with the transportation of people and cargo. The purpose of my thesis is to achieve the Enterprise value of Delta Air Lines, by applying different Firm Valuation methodology. With this, it is expected to give a formal opinion on the company’s shares. The chosen methodologies to perform the valuation model was the Discounted Cash Flows valuation (DCF) and the Multiples model. The DCF valuation was based on four main assumption: number of seats available, number of miles travelled, number of passengers and number of planes. For the Multiples valuation, the information from similar companies within the same industry was used, with the purpose of serving as benchmarked to the DCF model. In the end, the models created were compared with two different investments reports (Raymond James’ e Cowen’). This comparison yield that all models analysed reached similar share price between $64 to $67. Since the company’s shares are currently valued as $56, there is a favourable opinion to buy Delta Air Lines market share.